Some reflections on the writing of the history of Tahuantinsuyo from primary sources (quipus) - Urton, Gary (2019)
A possible redefinition of nature and content around Khipus «historical» information is revealed as a new way to approach the substance of these knotted textile record-keeping devices used by the Inkas. This article aims to reveal how a new history of Tawantinsuyu based in primary data can be written. This is the world about which Sabine McCormack wrote relevant essays with extraordinary erudition. In short, my argument defends that main khipus information refers to administrative or official statistics; so we’ll be able to write a real indigenous history of the Inka empire, specially if we redefine History, that is, if History is consists of more than just great men and great battles, if History can be written as a memory relationship of Economy, Demography and Society with Natural Environment.